2020
DOI: 10.1093/jas/skaa294
|View full text |Cite
|
Sign up to set email alerts
|

Fetal programming in sheep: effects on pre- and postnatal development in lambs

Abstract: This systematic review and meta-analysis aim to summarize the effects of maternal under or overnutrition during pregnancy on fetal weight and morphometric measurements during pregnancy, at birth and postnatal period in sheep. After completing the search, selection and data extraction steps, the measure of effect was generated by the individual comparison of each indicator with the average of the control and treated group (undernutrition or overnutrition) using the DerSimonian and Laird method for random effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Ewes in gestation and lactating have an increased nutritional requirement due to fetal growth, colostrum, and milk synthesis (NRC, 2007) and poor nutrition can result in metabolic diseases such as pregnancy toxemia [2]. However, maternal nutrition may affect lamb's body weight [3], development of the liver, lung, and pancreas [4], meat quality, and weight of premium cuts [5], and changes in bone tissue [6]. The fetal programming study is investigating the effect of maternal nutrition on offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Ewes in gestation and lactating have an increased nutritional requirement due to fetal growth, colostrum, and milk synthesis (NRC, 2007) and poor nutrition can result in metabolic diseases such as pregnancy toxemia [2]. However, maternal nutrition may affect lamb's body weight [3], development of the liver, lung, and pancreas [4], meat quality, and weight of premium cuts [5], and changes in bone tissue [6]. The fetal programming study is investigating the effect of maternal nutrition on offspring.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been observed in livestock species in response to maternal nutrient restriction during pregnancy with effects on fetal growth as well as skeletal muscle and pancreas function [ 5 – 8 ]. Additionally, maternal nutrient restriction during gestation has been shown to decrease postnatal growth rates in sheep progeny [ 9 11 ], pig progeny [ 12 ], and cattle progeny [ 13 , 14 ]. Furthermore, a number of cattle studies have reported reductions in economically important carcass traits such as hot carcass weight (HCW), yield grade, quality grade, and meat tenderness in response to maternal undernutrition [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequences on bone development and mineralization caused by maternal nutrition are less common to be observed (SARTORI et al, 2020).…”
Section: Development Of Muscle Adipose Tissue and Bonementioning
confidence: 99%
“…However, the formation of the placenta occurs earlier and maternal malnutrition can lead to a failure in placental development, consequently preventing the full growth potential of the fetus at the end of pregnancy (GREENWOOD; BELL, 2019b). Sartori et al (2020) published a review identifying studies with maternal under and overnutrition during pregnancy and its consequences on weight morphometric measurements of the progeny. This meta-analysis showed that effects of overnutrition are heterogeneous but those of undernutrition are consistent and influenced by litter size, time and duration of the intervention and overall reducing nutrient intake during pregnancy, mainly in the last third or during more than 90 days, produces lighter lambs, but does not influence their size.…”
Section: Fetal Organ Developmentmentioning
confidence: 99%
See 1 more Smart Citation